Characterization of diarrheagenic Escherichia coli from different cattle production systems in Brazil - de Melo Tavares, Rafaela; Sereno, Mallu Jagnow; Nunes da Cruz Encide Sampaio, Aryele [UNESP]; Pereira, Juliano Gonçalves [UNESP]; Bersot, Luciano dos Santos; Yamatogi, Ricardo Seiti; Call, Douglas Ruben; Nero, Luís Augusto (Elsevier, 2024)
Diarrheagenic E. coli (DEC) can cause severe diarrhea and is a public health concern worldwide. Cattle are an important reservoir for this group of pathogens, and once introduced into the abattoir environment, these microorganisms can contaminate consumer products. This study aimed to characterize the distribution of DEC [Shiga toxin-producing E. coli (STEC), enteroinvasive E. coli (EIEC), enteropathogenic E. coli (EPEC), enterotoxigenic E. coli (ETEC), and enteroaggregative E. coli (EAEC)] from extensive and intensive cattle production systems in Brazil. Samples (n = 919) were collected from animal feces (n = 200), carcasses (n = 600), meat cuts (n = 90), employee feces (n = 9), and slaughterhouse water (n = 20). Virulence genes were detected by PCR in 10% of animal samples (94/919), with STEC (n = 81) as the higher prevalence, followed by EIEC (n = 8), and lastly EPEC (n = 5). Animals raised in an extensive system had a higher prevalence of STEC (average 48%, sd = 2.04) when compared to animals raised in an intensive system (23%, sd = 1.95) (Chi-square test, P < 0.001). From these animals, most STEC isolates only harbored stx2 (58%), and 7% were STEC LEE-positive isolates that were further identified as O157:H7. This study provides further evidence that cattle are potential sources of DEC, especially STEC, and that potentially pathogenic E. coli isolates are widely distributed in feces and carcasses during the slaughter process.
Keywords: Animal reservoir; Brazil; Enterohemorrhagic E. coli O157:H7; STEC